1975
DOI: 10.1128/iai.11.5.904-907.1975
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping of Chlamydia: isolates of bovine origin

Abstract: Chlamydial isolates of bovine origin were serotyped by a plaque reduction method. Of the two major serotypes observed, type 1 included isolates from bovine abortion and enteric infections, whereas type 2 isolates were associated with polyarthritis or encephalomyelitis. These two serotypes were identical to those with a similar disease distribution previously observed in isolates of ovine origin. The two groups did not cross-react and they were serologically unrelated to chlamydiae of avian origin. Thus, it app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 8 publications
(4 reference statements)
2
26
0
Order By: Relevance
“…In order to predict time post infection at which optimal numbers of inclusions for any possible variant might be expected, a time study was undertaken. which also included a less cytopathogenic strain (29) of the same serotype (25). The efficiency of this system was finally compared with isolation in embryonated eggs, using different isolates from a clinical case.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In order to predict time post infection at which optimal numbers of inclusions for any possible variant might be expected, a time study was undertaken. which also included a less cytopathogenic strain (29) of the same serotype (25). The efficiency of this system was finally compared with isolation in embryonated eggs, using different isolates from a clinical case.…”
supporting
confidence: 56%
“…For C. trachomaris this work has promoted the understanding of chlamydia as an important etiological agent of especially venereal diseases of man in industrialized countries (24). For C. psirfaci, only including two serotypes (25). which are mainly restricted to infections in mammals and birds (281, experimental work with some strains, propagating readily in cell cultures without any artificial aid, has been reported (17, 16, 7, 2.…”
mentioning
confidence: 99%
“…Storz and his coworkers (28,32,33) showed 8 biotypes in avian and mammalian C. psittaci by analysis of morphological differences of inclusion bodies and biological effects of diethylaminoethyl (DEAE)-dextran and cycloheximide in their growth medium, and further revealed 9 immunotypes in mammalian C. psittaci by applying microimmunofluorescent test (MIF). Eb and Orfila (4) also confirmed the 2 serotypes of Schachter et al (30,31). Recently Anderson (1) reported serotyping by use of typespecific monoclonal antibodies to avian and mammalian C. psittaci.…”
Section: Introductionmentioning
confidence: 77%
“…Many efforts were attempted to classify C. psittaci. Schachter et al (30,31) showed 2 serotypes in mammalian C. psittaci using plaque neutralization tests. Storz and his coworkers (28,32,33) showed 8 biotypes in avian and mammalian C. psittaci by analysis of morphological differences of inclusion bodies and biological effects of diethylaminoethyl (DEAE)-dextran and cycloheximide in their growth medium, and further revealed 9 immunotypes in mammalian C. psittaci by applying microimmunofluorescent test (MIF).…”
Section: Introductionmentioning
confidence: 99%
“…The association of human psittacosis cases with psittacine birds and pigeons is well recognized (19,20,22). Serotyping or biotyping of C. psittaci has been reported by several investigators (4,18,20,24,25) ; however, their work dealt mostly with C. psittaci strains of mammalian origin, leaving serotyping of avian strains unexplored. In contrast, Chlamydia trachomatis strains have been divided into 15 serotypes by the micro-immunofluorescence test (MIFT) (14,27).…”
mentioning
confidence: 99%